Isolation and selection of local isolates of chitinolitic bacteria that potent to biocontrol of larva stadia of Aedes aegypti L. - SRI PUJIYANTO; ENDANG KUSDIYANTINI; MOCHAMMAD HADI (Society for Indonesian Biodiversity, 2008)
The dengue fever was the most dangerously epidemic in Indonesia, so it is important to prevent the population of Aedes aegypti L. The larva stages of Ae. aegypti had an exosceleton from chitin, so if its exosceleton had been degraded the larva would be died. Many bacteria had chitin degradation activities, and the bacteria had potential as a biocontrol for Ae. aegypti larva stages. This research was got many of the local chitinolitic bacteria that had been potential as a biocontrol for Ae. aegypti larva stages. The chitinolitic bacteria were isolated with selective agar medium. The sources of isolates were collected from Central Java and West Java water resources. Selected isolates was done to get the higher chitinolitic activity in mineral water medium. The isolate LMB1-5 was potential as a bioinsecticide for Ae. aegypti larva stages. This isolate decreased 86.7% of the larva population in 7 days.Â© 2008 Jurusan Biologi FMIPA UNS SurakartaKey words: chitinolitic bacteria, dengue fever, Aedes aegypti L, biocontrol